Alinhamento entre o sistema de inteligência competitiva e o gerenciamento da informação: estudo de caso em uma organização do setor de telecomunicação - Toledo, Luiz Alberto (2006)
In a world of still competition, the value of the information becomes an important component for the executives to drive their decisions in time so that they can react to the environmental adversities. The use of a system of competitive intelligence system may enathe the organization to have an edge over the competitors by using the information in intelligent way in the decision making process. Simultaneously with the use of this system, the information architecture and it s management through the technology may also also be considered as important components for the efficient use of the system of competitive intelligence. For this paper, a qualitative research was made by using the method of study of unique case. It was chosen an active company on the telecommunications market. The objectives of this paper were to verify the existence, the operation of a competitive intelligence system, the form for the information s management and the alignment between competitive intelligence system and the form of information management. The alignment between the intelligence system and the form of the information management can demonstrate how much the technology can be treated as an important resource for the company to sustain a strategy that can supply the competitive advantage.